Acute transfusion reactions at a national referral hospital in Uganda: a prospective study. Issue 11 (8th May 2014) - Waiswa, Musa K.; Moses, Ali; Seremba, Emmanuel; Ddungu, Henry; Hume, Heather A.
<x xml:space="preserve">Abstract</x> Background Very little has been published about acute transfusion reactions (ATRs) in developing countries. This study was undertaken to determine the incidence, type, imputability, severity, and possible associated factors of ATRs observed in a university‐affiliated hospital in Uganda. Study Design and Methods We prospectively followed the transfusion of blood units issued over a 7‐week period from the hospital blood bank during regular working hours to nonbleeding patients. For each transfusion, we recorded the patient's status before, during, at the end of, and 4 hours after transfusion. Three physicians independently reviewed all reports of suspected ATRs and related hospital charts. Using predefined criteria, the presence, type, imputability, and severity of ATRs were adjudicated by consensus of two of three physicians. Factors potentially associated with ATRs were analyzed for statistical significance. Results A total of 507 transfusions were analyzed. Fifty‐three acute transfusion events were recorded and 49 of 53 or 9.6% of the 507 transfusions were confirmed to be ATRs by physician consensus: 24 febrile, seven allergic, five hypertensive, three hypotensive, three transfusion‐associated circulatory overload, two acute hemolytic, and five others. Imputability of ATRs was definite, probable, or possible in 45 of 49 ATRs (92% of ATRs or 8.9% of transfusions) and judged to be severe in nine of 45. No significant associated factors were identified. Conclusions Our findings suggest that ATRs may occur more commonly in resource‐limited settings than in high‐income countries. Although some reactions are unavoidable, improved surveillance of transfusions and implementation of transfusion guidelines could improve the safety of transfusions in these settings.